Isolation and antibacterial activity of endophytic fungi from citronella grass (Cymbopogon nardus) - MUTHIA MUHARANI FAIS; YURNALIZA YURNALIZA; LIANA DWI SRI HASTUTI (Society for Indonesian Biodiversity, 2022)
Abstract. Fais MM, Yurnaliza Y, Hastuti LDS. 2022. Isolation and antibacterial activity of endophytic fungi from citronella grass (Cymbopogon nardus (L.) Rendle). Biodiversitas 23: 6564-6569. Endophytic fungi are a group of functional microorganisms from plants that can be used as a sustainable source to produce bioactive metabolites including pharmaceuticals. Citronella grass (Cymbopogon nardus (L.) Rendle) is a kind of medicinal plant that could be used to research the capabilities of endophytic fungi it harbors. The objective of this study was to isolate different endophytic fungi from leaves and stem of citronella plant that may be able to produce antibacterial substances. The bacteria Methicillin-resistant Staphylococcus aureus (MRSA) and Escherichia coli ATCC 25922 were used in plug agar method to determine the potency of endophytic fungi as antibacterials. Using ITS1F and ITS4R primers, endophytic fungal isolates were identified molecularly. Result showed that total 20 isolates of endophytic fungi were obtained from citronella, 15 isolates from stem and 5 isolates from leaves. Three fungal isolates i.e. CNB 254, CNB 253, and CND 111, exhibited highly potent antagonistic activity against tested bacteria. The ethyl acetate extract had a higher antibacterial ability than methanol extract based on the diameter of inhibition zone formed. The three potential isolates were molecularly identified and submitted to GenBank, such as Trichoderma atrobrunneum CNB 253 (OP584477), Trichoderma afroharzianum CNB 254 (OP584478), and Fusarium pernambucanum CND 111(OP584479). The results of this study revealed that citronella grass has a relationship with endophytic fungi that include strains that may be exploited as a source of antimicrobials.